Fluxes of dissolved aluminum and manganese to the Weddell Sea and indications for manganese co‐limitation. (27th December 2012) - Middag, Rob; de Baar, Hein J. W.; Klunder, Maarten B.; Laan, Patrick
Abstract : The trace metals aluminum (Al) and manganese (Mn) were studied in the Weddell Sea in March 2008. Concentrations of dissolved Al ([Al]) were slightly elevated (0.23–0.35 nmol L −1 ) in the surface layer compared to the subsurface minimum (0.07–0.21 nmol L −1 ) observed in the winter water. Atmospheric deposition is the main source of Al to the central Weddell Sea (22 µmol m −2 yr −1 ), and the residence time of dissolved Al in the upper mixed layer is ∼ 0.8 yr. The flux from the shelf and slope regions equals about 50% of the atmospheric input of Al to the western Weddell Sea. The highest [Al] in the Weddell Sea bottom water (WSBW) is related to the formation of deep water, and the associated downward flux is in the range of 3–10 µmol Al m −2 yr −1 . The concentrations of dissolved Mn ([Mn]) were depleted in the surface layer, likely as a result of biological uptake, as indicated by the correlation among Mn, major nutrients, and fluorescence. The significant negative relation between the ΔMn : ΔP ratio and the ambient concentration of dissolved iron indicates iron‐Mn co‐limitation. The flux of Mn from the continental margin is about 2.2 times greater than atmospheric input (1.1 µmol m −2 yr −1 ). The flux of both Al and Mn from the continental margin indicates melting of continental ice (icebergs) or direct continental runoff. The slightly elevated [Mn] in the WSBW is due to a relatively small flux of 1 µmol Mn m −2 yr −1 associated with WSBW formation.